Addressing Discrepancies Between ADHD Prevalence and Case Identification Estimates Among U.S. Children Utilizing NSCH 2007-2012. Issue 14 (December 2019) - Song, MinKyoung; Dieckmann, Nathan F.; Nigg, Joel T.
Objective: Among U.S. children, ADHD epidemiological estimates (3%-5%) vary significantly from case identification rates (over 11%), leading to confusion about true incidence and prevalence. We investigated the extent to which this discrepancy could be resolved by definitional issues through reexamining the most cited U.S. survey of case identification, the National Survey of Children's Health (NSCH).Method: Using NSCH 2007/2008 and 2011/2012, we stratified identification of ADHD by current status, severity, psychiatric comorbidity, and ADHD medication usage. Using those criteria, definitional strength was coded into "Definite, " "Probable, " "Doubtful, " and "No."Results: "Definite" ADHD in caseness in 2007/2008 was 4.04%, increasing to 5.49% in 2011/2012, roughly corresponding to epidemiological estimates. "Definite" ADHD was the primary contributor to an overall increase in caseness over that period.Conclusion: This analysis strengthens understanding of discrepancies in estimated ADHD rates. When low confidence identification is considered false positives, ADHD case identification rates match epidemiological estimates more closely.